2003
DOI: 10.1084/jem.20030495
|View full text |Cite
|
Sign up to set email alerts
|

Normal Induction but Attenuated Progression of Germinal Center Responses in BAFF and BAFF-R Signaling–Deficient Mice

Abstract: The factors regulating germinal center (GC) B cell fate are poorly understood. Recent studies have defined a crucial role for the B cell–activating factor belonging to TNF family (BAFF; also called BLyS) in promoting primary B cell survival and development. A role for this cytokine in antigen-driven B cell responses has been suggested but current data in this regard are limited. A BAFF receptor expressed by B cells (BAFF-R/BR3) is defective in A/WySnJ mice which exhibit a phenotype similar to BAFF-deficient (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
187
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(210 citation statements)
references
References 63 publications
(121 reference statements)
21
187
0
2
Order By: Relevance
“…via lymphotoxin b). In BAFF-R-null mice, however, FDC networks are present but B cells fail to proliferate, possibly because TACI and/or BCMA signals, in the absence of BAFF-R, prevent cell cycle progression [42]. In this respect, it is interesting to note that human germinal center B cells express BCMA [39 ].…”
Section: Surface Markers and Germinal Centersmentioning
confidence: 99%
See 1 more Smart Citation
“…via lymphotoxin b). In BAFF-R-null mice, however, FDC networks are present but B cells fail to proliferate, possibly because TACI and/or BCMA signals, in the absence of BAFF-R, prevent cell cycle progression [42]. In this respect, it is interesting to note that human germinal center B cells express BCMA [39 ].…”
Section: Surface Markers and Germinal Centersmentioning
confidence: 99%
“…[40] Switching to IgA and IgG occurs [50] Reduced Increased number [45] Impaired + [35] Normal in PP and mLN GCs [40] Impaired + No Ki67 in B cells [42] Marginal zone B cells…”
Section: Baff-independent B-cell Survivalmentioning
confidence: 99%
“…25 Immunohistology was performed using the antibodies listed above and the stained sections were analyzed using a fluorescence microscopy (Leitz Diaplan, Wetzlar, Germany) and images were captured as described. 26 Flow cytometry Four-color flow cytometric analysis was performed on cell suspensions prepared from spleens of naive and immunized mice stained with multiple combinations of antibodies listed above. Biotinylated Abs were detected with SA-CyChrome.…”
Section: Immunohistologymentioning
confidence: 99%
“…We have shown that a CD40 agonist coupled with a TD antigen ablates long-lived humoral immunity in favor of short-lived extrafollicular PCs, with this situation partially mimicked in vivo by enhancing T-cell help [19]. Other factors that impact the B cell include the interactions of BAFF (B-cell activating factor belonging to the TNF family) and APRIL (a proliferation inducing ligand) with their B-cell expressed receptors, Tolllike receptor ligation, cytokines and downstream signaling mediators of the BCR such as Lyn tyrosine kinase, which can attenuate or exacerbate total signal strength to the GC B cell and thus influence terminal B-cell differentiation [24][25][26][27].…”
Section: B-cell Destiny Controlled By Bcr Affinitymentioning
confidence: 99%